2005
DOI: 10.1089/cpb.2005.8.52
|View full text |Cite
|
Sign up to set email alerts
|

Flirting on the Internet and the Hickey: A Hermeneutic

Abstract: Nowadays, erotic behaviour in cyberspace is customary. Online dating is a million dollar industry. Within the everyday politics of erotic-romantic relationships, however, males and females still blush in each other's presence, caress tenderly and trade hickeys. Mainstream social science researches cyber-behaviour voluminously, but totally ignores commonplace fleshy phenomena. Our study probes this discrepancy. What does it mean that virtual sex is winning the current war between desire and technology? Why is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…Unfortunately, however, these tactile aspects of communication are completely lacking in long-distance interactions (such as in telephone calls or in internet-based communications). As pointed out by Alapack (2007), nothing, not a fantasy, nor 'a text vanishing at the click of the mouse', can compensate for the lack of flesh-to-flesh contact in virtual communication and/or relationships (see also Alapack et al, 2005). Although many efforts have been made to ameliorate the visual and auditory aspects of on-line relationships, very little progress has been made toward adding physical contact to internet and long-distance interactions.…”
Section: Interpersonal Touch In the Era Of Virtual Communicationmentioning
confidence: 99%
“…Unfortunately, however, these tactile aspects of communication are completely lacking in long-distance interactions (such as in telephone calls or in internet-based communications). As pointed out by Alapack (2007), nothing, not a fantasy, nor 'a text vanishing at the click of the mouse', can compensate for the lack of flesh-to-flesh contact in virtual communication and/or relationships (see also Alapack et al, 2005). Although many efforts have been made to ameliorate the visual and auditory aspects of on-line relationships, very little progress has been made toward adding physical contact to internet and long-distance interactions.…”
Section: Interpersonal Touch In the Era Of Virtual Communicationmentioning
confidence: 99%
“…Dem ersten Treffen kommt eine bedeutende Rolle zu, weil erstmalig die Passung im realen Setting bewertet werden kann (Abramova et al 2016;Khan und Chaudhry 2015). Stimme, Sprechweise, Mimik, Gestik, Geruch und andere für die sexuelle Attraktion zentrale Charakteristika sind in der schriftlichen Selbstdarstellung und Interaktion nicht vermittelbar und führen bei telefonischem oder persönlichem Kontakt schnell zu Enttäuschungen; zumindest dann, wenn das Gegenüber nicht den im Online-Kontext vermittelten Eindrücken entspricht (Alapack et al 2005;Cacioppo et al 2013). Daher kann es beim Wechsel vom Online-zum Offline-Kontakt zu einem Bruch kommen, wenn das subjektive Bild von der Person nicht mit der Realität übereinstimmt (Dröge 2013).…”
Section: Face-to-face-treffenunclassified
“…(e) Letting someone know that you like them. Determining appropriate ways to let someone know that you are attracted to them or interested in pursuing a friendship/relationship (Alapack, Blichfeldt, & Elden, 2005). refraining from engaging in cyberbullying with another person (Li;Privitera & Campbell, 2005).…”
Section: Gaggle (2010)mentioning
confidence: 99%
“…Ducehneaut and Moore (2005) identified several skills needed to succeed in an online role-playing game: (a) having a conversation with someone you do not know, (b) being sensitive to statements individuals make to each other, (c) collaboration among players, (d) waiting turns to participate, and (e) having empathy for other players. In addition to these skills, researchers have indicated that a large percentage of users of online social environments spend time sharing feelings of attraction for each other and discussing ways to address these feelings (Alapack, Blechfeldt, & Elden, 2005). There has also been indication that users lie about information in online environments and the amount of personal information shared, resulting in safety issues (Boyd, 2008; Harman et al, 2005; Potter & Potter, 2001).…”
Section: Social Skills Instruction In School Environmentsmentioning
confidence: 99%